Philosophy of Mathematics and Mathematical Practice in the Seventeenth Century. - Mancosu, Paolo (Oxford University Press, 1996)
The 17th century saw a dramatic development in mathematical theory and practice. This is an account of the foundational issues raised in the relationship between mathematical advances of the period and the philosophy of mathematics.